The achievements of medieval archaeology in the past fifty years - Melkonyan, Husik (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
The study of the material culture and historical-architectural sites of medieval Armenia began in the middle of the 19th century and was connected to the topographical surveys conducted at the time. Scholars were exploring different regions of the country, recording sites, describing the materials that had been discovered by chance at those sites, as well as copying and publishing epigraphic inscriptions. The foundations of these scholarly endeavors are connected with the Caucasian Museum, which was founded in Tiflis (Tbilisi) in 1850s. The materials discovered in various excavations in South Caucasia were being collected here. The majority of the materials were later transferred to Yerevan.